Manejemen Kualitas Air di Sungai Sigeleng Desa Randusanga Kulon Brebes - Barkah, Atiyah; Setiyawan, Gunanto (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
Development in developing countries is meant to yield development progress, although usually followed by environmental damage. This problems is caused by the act of human being which heedless of the conservation aspect. One of its impact is low quality of water river.This condition can be observed by the indication of low dissolve oxygen Concentration (DO), high biological oxygen requirement concentration (BOD), and high suspended soil ( SS). This condition can causes damage to environment and ecology inbalance. Resident growth, animal husbandry and compost heap in the Sigeleng River of Randusanga Kulon Village, Brebes of Central Java, have resulted the water contamination. Therefore, expected with the approach of inwrought water quality management studying goodness from law aspect, technical, economics and society can be existed by a make-up of environmental quality in the Sigeleng River Sigeleng at  years to come. In addition, from the observation water quality, the fluoride (F) content at least 1.702 mg/l > 1.500 mg/l (the permissible value), the timbale (Pb) content at least 0,275 mg/l >0,100 mg/l the fluoride and Chemical oxygen demand (COD) content at least 160 mg/l  > 50 mg/l. Ti increase the qualities of that water resources as become fresh water, it can be efforted of treatment for the neutralize using of contant F, Pb and COD. Threatment of water quality i.e.  sedimentation, filtration, and chemical prosses such as  activated carbonation and ziolith sand. Keywords: water quality managementPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3912[How to cite: Barkah, A. dan Setiyawan, G., 2005, Manejemen Kualitas Air di Sungai Sigeleng Desa Randusanga Kulon Brebes, Jurnal Media Komunikasi Teknik Sipil, Voume 13, Nomor 2, pp. 85-93]